Incidence of second primary cancers in patients with retinoblastoma: a systematic review and meta-analysis - Sun, Jinfeng; Gu, Xiuli; Wang, Liangjun (Frontiers in Oncology, 2024)
Emerging studies reported the long-term risk of second primary cancers (SPCs) among hereditary and nonhereditary retinoblastoma (Rb) patients. However, there has yet to be a comprehensive systematic review to synthesize the existing evidence. Therefore, this systematic review and meta-analysis aimed to examine the risk of SPCs among Rb patients. PubMed, EMBASE, and Cochrane Library were searched for eligible studies from inception to 12 March 2023. We also retrieved articles by manual screening. The primary outcome was the standardized incidence ratios (SIRs) of SPCs in Rb patients. Summary estimates were calculated using a random or fixed effects model. Ten studies were included in this review. There were nine high-quality studies based on the Newcastle-Ottawa Scale. The summary estimate of SIR for SPCs was 17.55 (95% CI=13.10-23.51) among hereditary Rb patients, and the pooled estimate of SIR for SPCs was 1.36 (95% CI=0.90-2.04) among nonhereditary Rb patients. The summary estimate of SIR for different SPC types had significant differences (P=0.028), including nasal cavity tumor (SIR=591.06, 95% CI=162.79-2146.01), bone tumor (SIR = 442.91, 95% CI=191.63-1023.68), soft tissue sarcoma (SIR=202.93, 95% CI=114.10-360.93), CNS (SIR=12.84, 95% CI=8.80-18.74), and female breast cancer (SIR=3.68, 95%CI =2.52-5.37). Chemotherapy and radiation therapy increased the risk of SPCs among hereditary Rb patients. Our findings suggested that patients with hereditary Rb had a significantly elevated risk for SPCs, while those with nonhereditary Rb did not. Significant differences were found between different SPC types. Treatment techniques also increased the risk of SPCs among hereditary Rb patients. Therefore, the physician should pay attention to radiation protection for Rb patients.